The Idea of Criticism in Abdullah Pashew’s Poetry - Abdullah Yassin Amedi; Mohammed Omer Ibrahim (QALAAI ZANIST JOURNAL, 2021)
This research consists of two essential parts. The first part presents the theoretical framework of the study; it discusses literary criticism, criticism from the perspective of language, criticism from a theoretical perspective and the purpose of literary criticism. The second part of research sheds light upon the types of criticism in Abdulla Pashew’s poetry such as political criticism, social criticism, criticism at war, and urge for peace. Pashew’s critiques of classism, his urge to revive Kurdish culture, his critique of the world powers for their silence over the Kurdish discrimination have been highlighted. At the end of the research, researchers conclude that Pashew, as a contemporary poet, depicts the real situation of Kurdish society in the 21th century. He has used his poetry to criticize politics and portray the wrongdoings and corruptions of the rulers of Iraqi Kurdistan. His poetry also proves that the rights of Kurdish have been violated.